Arab music ; a survey of its history and its modern practice - Plenckers, Leo J. (Archaeopress Publishing Ltd, 2021)
Offering a comprehensive survey of the history and the development of Arab music and musical theory from its pre-Islamic roots until 1970, this book also offers a discussion of the major genres and forms practiced today, such as the Egyptian gil, the Algerian raï and Palestinian hip hop; it also touches upon musical instruments and folk music.